2014
DOI: 10.3148/cjdpr-2014-008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Healthy Eating and Active Lifestyle Issues through Photo Elicitation

Abstract: Photo elicitation was determined to be an effective technique to engage participants. Despite many supports, members of the university community still found it difficult to follow healthy eating and active lifestyle behaviours; however, a number of practical future supports were identified. This study also provided valuable insight into the role that dietitians can play in the development of successful wellness programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Joy et al used photo elicitation with volunteer University members (students n = 11, employees n = 14) to identify healthy eating and active lifestyle barriers and supports. Similar to our findings, participants reported that on campus, physical activity was principally possible, but dysfunctional (e.g., overgrown) walkways were regarded as barriers ( 18 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Joy et al used photo elicitation with volunteer University members (students n = 11, employees n = 14) to identify healthy eating and active lifestyle barriers and supports. Similar to our findings, participants reported that on campus, physical activity was principally possible, but dysfunctional (e.g., overgrown) walkways were regarded as barriers ( 18 ).…”
Section: Discussionsupporting
confidence: 87%
“…Since its inception, the Photovoice methodology has been applied to a variety of populations, places, health issues, and disciplines. Some studies have performed Photovoice with adolescents, in order to capture their perspectives on health and well-being ( 17 ), healthy eating and active lifestyle barriers ( 18 ), or sexual health information, alcohol and drugs ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several of these articles address conflict of interests, sponsorships and partnerships in public health and nutrition [ 27 30 ] . The other articles focus on behaviors, perceptions and food choice motives [ 31 33 ], nutritionism and the ethics of the commercialization of food [ 34 ], and the implications for public health of appropriate information to consumers and health claims linked to polyphenols [ 35 ].These articles are not discussed further in this paper, but are included in the statistics.…”
Section: Methodsmentioning
confidence: 99%
“…This methodology has also been effective in researching patient health experiences. Specifically, photos have been used as integral components in studies of the experiences of adolescents with established renal failure [18], women's experiences of chemotherapy [19], and employees' perceptions and barriers to healthier dietary and physical activity choices [20]. Furthermore, visual methods have been shown to be useful in developing health promotion messages to encourage physical activity with older Hispanic women [21].…”
Section: Methodsmentioning
confidence: 99%